Global development finance : country tables. - The World Bank. (Washington, D.C. : The World Bank, 1998)
Tracks the annual movement of international capital flows to develop ing countries and discusses selected analytical and policy issues in in ternational finance for developing countries. Provides a review of deve loping countries' external debt and financial flows as well as consolid ated statistics for all developing countries.
Title from disc label.
System requirements: IBM-compatible Pentium; 32MB RAM; Windows 95 or Windows NT 4.0; 20MB free hard disk space; 2MB video memory; CD-ROM dr ive.
Keywords: Loans, Foreign -- Developing countries -- Statistics; Debts, External -- Developing countries -- Statistics; International finance -- Statistics